While studying Ramanujan's Collected Papers I came across an identity $$q(1 + q + q^{3} + q^{6} + \cdots)^{8} = \frac{1^{3}q}{1 - q^{2}} + \frac{2^{3}q^{2}}{1 - q^{4}} + \frac{3^{3}q^{3}}{1 - q^{6}} + \cdots$$ which I am unable to establish (although the identity looks simple). I tried to use the the following identities:

$\displaystyle Q(q) = 1 + 240\left(\frac{1^{3}q}{1 - q} + \frac{2^{3}q^{2}}{1 - q^{2}} + \frac{3^{3}q^{3}}{1 - q^{3}} + \cdots\right) = \left(\frac{2K}{\pi}\right)^{4}(1 + 14k^{2} + k^{4})$

$\displaystyle Q(-q) = \left(\frac{2K}{\pi}\right)^{4}(1 - 16k^{2} + 16k^{4})$

$\displaystyle Q(q^{2}) = \left(\frac{2K}{\pi}\right)^{4}(1 - k^{2} + k^{4})$

where we have $q = e^{-\pi K(k')/K(k)}$ and was trying to put the RHS (of the identity to be established) as a combination of the above $Q$ functions but was not able to do so. In this way I thought to transform the RHS in terms of $K, k$ and then reach the LHS which is $q\psi^{8}(q)$ where Ramanujan's $\psi(q)$ is related to Jacobi's theta function via $\vartheta_{2}(q) = 2q^{1/4}\psi(q^{2})$. I was able to write the RHS as

$\displaystyle \sum_{n = 1}^{\infty}\frac{n^{3}q^{n}}{1 - q^{2n}} = \frac{1}{2}\sum_{n = 1}^{\infty}\frac{n^{3}q^{n}}{1 - q^{n}} + \frac{1}{2}\sum_{n = 1}^{\infty}\frac{n^{3}q^{n}}{1 + q^{n}} = S_{1} + S_{2}$

where $S_{1}$ can be expresssed in terms of $Q(q)$, but somehow could not express $S_{2}$ in terms of $Q$ functions. Maybe I am on the wrong path. If there is any simpler way to prove the identity please let me know.

  • $\begingroup$ Using $Q(q)$ was more to the point. $R(q)$ uses $n^5$, not $n^3$. $\endgroup$ – ccorn Jul 9 '13 at 11:33
  • $\begingroup$ Sorry ccorn, it seems I got carried away due to some other thoughts. Now it is back to the earlier version. Hopefully it will not cause any further confusion. By the way I liked the rollback feature in editing. $\endgroup$ – Paramanand Singh Jul 9 '13 at 11:36
  • $\begingroup$ It might already help you if you use not the "plus" partial fraction decomposition but the "minus" one which delivers a factor $q^n$ for free in the expansion of $Q(q) - Q(q^2)$. $\endgroup$ – ccorn Jul 9 '13 at 11:51
  • $\begingroup$ ccorn, but in that case the individual series would not converge as $n^{3}/(1 - q^{n})$ wont tend to zero as $n \to \infty$. I had first thought of that but then rejected it. $\endgroup$ – Paramanand Singh Jul 9 '13 at 11:54
  • $\begingroup$ Yes, that's why I added "in $Q(q)-Q(q^2)$" afterwards, sorry. $\endgroup$ – ccorn Jul 9 '13 at 11:55

Paramanand Singh already found the answer. Nevertheless I'll try to post an answer here.

To avoid issues with branch cuts of $K$, let us replace $$\frac{2K}{\pi} = \vartheta_3^2(q);\quad k = \frac{\vartheta_2^2(q)}{\vartheta_3^2(q)}$$ where $$\vartheta_3(q) = \sum_{n\in\mathbb{Z}} q^{n^2}$$ is another Jacobi thetanull function. Thus $$Q(q)-Q(q^2) = 15\,\vartheta_2^4(q)\,\vartheta_3^4(q)$$

Now use the doubling formula: $$\vartheta_2^2(q) = 2\,\vartheta_2(q^2)\,\vartheta_3(q^2)$$

Therefore $$Q(q)-Q(q^2) = \frac{15}{16}\vartheta_2^8(q^{1/2}) = 240\,q\,\psi^8(q)$$

Consequently, your LHS equals $$q\,\psi^8(q) = \frac{1}{240}\left(Q(q)-Q(q^2)\right) =\sum_{n=1}^\infty\left(\frac{n^3\,q^n}{1-q^n} -\frac{n^3\,q^{2n}}{1-q^{2n}}\right)$$ $$= \sum_{n=1}^\infty n^3\,\frac{q^n\,(1+q^n)-q^{2n}}{1-q^{2n}} = \sum_{n=1}^\infty \frac{n^3\,q^n}{1-q^{2n}}$$ which is the RHS, QED.

(Edit: typo corrections.)

  • $\begingroup$ Note: When thinking in terms of functions instead of formal power series, we have to assume that $|q|<1$ so the series converge absolutely. $\endgroup$ – ccorn Jul 9 '13 at 13:03

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.